Analisis Pengaruh Jumlah Industri, Nilai Investasi, Dan Nilai Produksi Terhadap Penyerapan Tenaga Kerja Sektor Industri Kecil Dan Mikro Di Jawa Timur - Melia Kusuma Dewi; Yunan Syaifullah (Jurnal Ilmu Ekonomi, 2022)
The economic development of a country or region is basically closely related to human resources, natural resources, technology, capital, and others. The role of humans is very important to manage, develop and develop their regions both economically and with workforce readiness. The success of regional economic development can be measured by high economic growth and increased employment. The economic growth approach is widely used in several regions in developing regional economic sectors which are expected to increase employment. The absorption of Regency and City workers in East Java shows that they are in the medium category, the lowest employment is in Batu City as many as 20,000 workers throughout 2016-2020. The number of IKM, Regency and City businesses in East Java is in the medium category, namely 18 districts and cities from 37 districts and cities. There are 8 districts and cities in the high category where the largest number of IKM companies are in Malang district with a total of 39,970 companies. Meanwhile, judging from the investment value in the medium category, only Malang and Surabaya regencies are included in the high category. And the production value there are 5 districts and cities with a high category where Malang Regency is one of the largest with an average of 8.177.